Community, Population, and Organization Effects on Innovation: A Multilevel Perspective - Drazin, Robert; Schoonhoven, Claudia Bird (Academy of Management Journal, 1996)
Two distinct themes emerge from the Special Research Forum on Innovation and Organizations. One group of articles develops an expanded view of the influence of context on organizations' ability to innovate. Together, the articles offer a complex multilevel view of context as including elements ranging from the dominant strategy of an organization to the social-psychological antecedents of creativity. A second group of articles provides a community and population perspective on the diffusion of innovations. We suggest the possibility of a union between the context and industry dynamics approaches.